Experimental and computational investigations on mechanically alloyed Fe55Co30Ni15 powders - Abdelkrim Houssou; Samia Amirat; Hana Ferkous; Safia Alleg; Karima Dadda; Rahima Boulechfar; Lakhdar Abadlia; Wahiba Bouchelaghem; Javed Khan Bhutto; Maha Awjan Alreshidi; Krishna Kumar Yadav; Noureddine Elboughdiri; et al. (Powder Technology, 2023)
Nanocrystalline Fe55Co30Ni15 powder alloy was created via mechanical alloying in a planetary ball mill (Fritsch P7) under an argon atmosphere. Structural, microstructural, and magnetic features were analyzed using X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDX), and vibrating sample magnetometry (VSM). The results indicated a coexistence of body-centered cubic (BCC) and face-centered cubic (FCC) solid solutions, with BCC being predominant (96%) and displaying an average grain size of 11 nm. Both BCC and FCC phases exhibited a significant density of dislocations (~1016 per square meter). The powder alloy demonstrated soft magnetic behavior with a saturation magnetization of 206.5 emu/g and a coercivity of 32.63 Oe, indicative of multidomain properties based on the Mr./Ms. ratio. Theoretical analysis confirmed precise computational simulation parameters at room temperature.
Keywords: Mechanical alloying Microstructure Magnetic properties Hyperfine structure